IJCM_186A: A cross sectional study to assess the prevalence of usage of online health apps and sleep quality among general population residing in Rajnandgaon city. - Vaishnav Shivangi; Verma Nirmal; Jaiswal Prashant (Indian Journal of Community Medicine, 2024)
Background: The purpose of this study is to examine and determine the design and content elements of health app that facilitate usage from user perception. Objectives: The object of the study is to find out the perception and usage of health app and the quality of sleep among general population. Methodology: A study conducted in Rajnandgaon with a mixture of smartphone owner of various socio-economic status. The participant was asked about their general and health specific mobile app usage and their sleep cycle. Results: 87.9% of the study participant were Smartphone user, out of which 48.6 % uses mobile health app to improve their health and out of which 51.4% would like to receive information about a healthy lifestyle in their smartphone.60% of smartphone user were male, 97.7% were Hindu and 71.1% were married. Among all user 97.2% were from class III and above. Conclusion: The regular use of medical apps on mobile devices is quite common among general population residing in Rajnandgaon, Chhattisgarh, India. The increasing usage of medical apps on smart devices is an established reality. The present study reveals that majority of population were aware of the Health apps. Many of them were willing to continue using it as it motivates them to do their physical activity regularly.